TerraTimber Nexus / Nabil Hasyiri Abdul Rahman ... [et al.] - Abdul Rahman, Nabil Hasyiri; Ahmad Zamzuri, Nur Syahmina; Jamaluddin, Nur ‘Alyaa Mahirah Solehah; Mohamed, Abdul Hamid (2024)
This abstract proposes an innovative approach to address the Fusion Timber Challenge by creating an eco-friendly centre for students at Universiti Teknologi MARA (UiTM), Seri Iskandar, Perak. This study investigates the incorporation of eco-friendly practices into architectural design, with a specific focus on the use of fusion timber, a sustainable alternative to traditional timber materials. The suggested eco-friendly hub aims to create a conducive environment for student activities while minimising its environmental impact. This involves integrating waste reduction, renewable resource usage, and energy efficiency concepts into the design process. The hub aims to reconcile usefulness, aesthetics, and environmental responsibility in a single structure by utilising green technologies, sustainable materials, and passive design principles. The project emphasises the importance of community engagement and education in promoting sustainable practices among lecturers and students. The hub serves not only as a physical space but also as an encouragement for positive behavioural change towards a greener future.